Interception of nutrient groundwater drich submarine discharge seepage on European temperate beaches by the acoel flatworm, Symsagittifera roscoffensis - Carvalho, Liliana Faia (2013)
Submarine groundwater discharge (SGD) occurs in intertidal areas, representing a largely unquantified source of solute fluxes to adjacent coastal zones, with nitrogen being constantly the keynote chemical of concern. In Olhos de Água SGD is present as groundwater springs or merely sub-aerial runoff. The occurrence of the flatworm Symsagittifera roscoffensis is described for the first time in Olhos de Água in connection to seepage flows. To assess the impact of this symbiotic flatworm on the nitrogen associated to groundwater discharge flow at the beach, nitrate uptake experiments were conducted in laboratory microcosms. Our results show that S. roscoffensis actively uptakes nitrate at different rates depending on light availability, with rates ∼10 times higher than that of its symbiotic microalgae alone. This supports the hypothesis thatS. roscoffensis could be an important in situ nitrate interceptor, potentially playing a biological role on the transformation of groundwater-borne nitrate loads at the land–ocean boundary.